Idiopathic Acquired Hemophilia A, a Rare Cause of Bleeding: A Case Report and Literature Review (2021)
ABSTRACT: BACKGROUND Acquired hemophilia is a bleeding disorder mediated by an autoimmune process, in which antibodies against clotting factors are developed. This is a rarely suspected complex condition in which the initial manifestations are spontaneous bleeding in the skin, soft tissues, and mucosa in patients with no known history of bleeding disorders. Most of the cases are idiopathic (50%), but it can be associated with autoimmune diseases, malignancy, pregnancy, and medications. The most frequent type is mediated by inhibitors against factor VIII, followed by coagulation factor IX and XI. It is a disease with high morbidity and mortality rates without adequate treatment. Diagnosis is based on the detection of low concentrations of clotting factors and the presence of an inhibitor. CASE REPORT We present 2 cases of patients with spontaneous bleeding in whom the diagnosis of idiopathic acquired hemophilia A was made, an extensive malignancy study was performed that was negative, and the presence of autoimmunity markers (positive antinuclear antibodies (ANA)) was observed, without any another sign of autoimmune disease. They received immunosuppressive therapy with bleeding control and inhibitor eradication. CONCLUSIONS Acquired hemophilia A is a rare but potentially lethal disease, representing a medical challenge from its diagnosis to its treatment. An early recognition and treatment are fundamental because delays are associated with adverse outcomes. Optimal management includes the workup and treatment for an underlying disease, use of "bypass" agents when active bleeding presents, and inhibitor titer eradication through immunosuppressants drugs. With the present cases, we highlight the importance of considering acquired hemophilia A in older patients with similar symptoms, to achieve early diagnosis and treatment.